Something Happening Quietly: Owen McCafferty's Theatre of Truth and Reconciliation. (November 2017) - Parr, Connal
Abstract : This article concerns the Belfast dramatist Owen McCafferty (1961–) and his play Quietly, which debuted at the Abbey's Peacock Theatre in November 2012. Considering antecedents in McCafferty's earlier work, it illustrates how the play reflects a longstanding and contemporary condition whereby individuals in Northern Ireland deal with the legacy of the Troubles on their own terms, essentially bypassing elected representatives engaged in polemical disputes over the past. Based on a real bombing in 1974, the production's development is outlined prior to discussions of the play's depiction of violence, racism, women, and the prospects of an independent truth commission and 'healing'.